Wickerhamomyces anomalus blood stream infection in a term newborn with pneumonia - Yılmaz Semerci, Seda; Demirel, Gamze; Taştekin, Ayhan (Turkish J Pediatrics, 2017)
The incidence of invasive candidiasis is high in neonates admitted to neonatal intensive care unit and is associated with significant morbidity and mortality rates. Candida albicans is the most common fungal agent pathogenic to neonates but invasive fungal infections caused by uncommon fungi have increased in recent years. Wickerhamomyces anomalus is a very rare pathogen causing blood stream infection in neonates, which has reportedly caused only few cases in the literature. Here we report a case of blood stream infection caused by a fungal agent Wickerhamomyces anomalus in a term male infant.
WOS: 000422968000021
PubMed ID: 29376586
Keywords: Wickerhamomyces Anomalus; Candidiasis; Newborn